On Search for Unconventional Energy Sources for Harvesting - Paweł Ligęza (Energies, 2024)
Energy transformation requires replacing power plants based on fossil raw materials with renewable energy. Energy harvesting plays an important, although not fully appreciated, role here. Distributed, local power supply systems for small receivers, based on various sources which previously dissipated energy, may contribute to changing the current energy paradigm. This article presents an overview of energy harvesting technologies and various energy sources used in this process. Particular attention was paid to sources of a less conventional nature. The aim of this article is to encourage and direct scientists with the potential to explore this topic to look for new, previously unexploited energy sources and innovative and effective methods of obtaining useful energy in the harvesting process.